RETRACTION Yewen, O., Widiyanto, W., Padli, P., Sabillah, M. I.., Zarya, F.., Haryanto, J.., Geanta, V. A.., Ndayisenga, J.., Falahudin, A.., Salahudin, S., Furkan, F., & Ardiansyah, A.. (2024). Aumento de la potencia muscular de las piernas y la fuerza muscular de los brazos de los atletas de baloncesto: a través de método de entrenamiento complejo y entrenamiento de peso corporal en circuito (Increased leg muscle power and arm muscle strength of basketball athletes: through complex training method and circuit body weight training). Retos, 60, 1213–1221. https://doi.org/10.47197/retos.v60.107239 - RETOS, RETOS (Retos, 2025)
Yewen, O., Widiyanto, W., Padli, P., Sabillah, M. I.., Zarya, F.., Haryanto, J.., Geanta, V. A.., Ndayisenga, J.., Falahudin, A.., Salahudin, S., Furkan, F., & Ardiansyah, A.. (2024). Aumento de la potencia muscular de las piernas y la fuerza muscular de los brazos de los atletas de baloncesto: a través de método de entrenamiento complejo y entrenamiento de peso corporal en circuito (Increased leg muscle power and arm muscle strength of basketball athletes: through complex training method and circuit body weight training). Retos, 60, 1213–1221. https://doi.org/10.47197/retos.v60.107239Retraction of the article by the editor of the journal. There has been several clear and conclusive proofs that there has been a manipulation of the authorship of the article. The accepted Word document was sent with the names of the authors that appeared in the “Corrections for the edition” message so that they could only make the orthographical corrections that were necessary. The corresponding author (or whoever hurt him) changed the authors of the aforementioned Word document that was sent to them, returning a document together with these corrections made with new authors, all without any express notification, without any document explaining the changes made accepted by all the authors and, of course, without express authorization from the journal Retos between both moments. With this fraudulent document the galleys were made and the article was definitively published, assigning it the corresponding DOI.Authors in the Word document of the article submitted for review: 9Authors in the published PDF with modified authors: 12Differences between the authors between both moments: +6 y -3 (Additions: Widiyanto, Jeki Haryanto, Japhet ndayisenga, Ardhika Falaahudin, Salahudin, Furkan. Eliminated: Bernadeta Suhartini, Khairani Faizah, Salahudin Salahudin)